2017
DOI: 10.1002/anie.201705787
|View full text |Cite
|
Sign up to set email alerts
|

Diradicaloid or Zwitterionic Character: The Non‐Tetrahedral Unsaturated Compound [Si4{N(SiMe3)Dipp}4] with a Butterfly‐type Si4 Substructure

Abstract: The reduction of the tribromoamidosilane {N(SiMe )Dipp}SiBr (Dipp=2,6-iPr C H ) with potassium graphite or magnesium resulted in the formation of [Si {N(SiMe )Dipp} ] (1), a bicyclo[1.1.0]tetrasilatetraamide. The Si motif in 1 does not adopt a tetrahedral substructure and exhibits two three-coordinate and two four-coordinate silicon atoms. The electronic situation on the three-coordinate silicon atoms is rationalized with positive and negative polarization based on EPR analysis, magnetization measurements, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 49 publications
2
47
0
7
Order By: Relevance
“…We recently reported on a bicyclic silicon ring compound Si 4 {N(SiMe 3 )Dipp} 4 1 with two three‐coordinate Si atoms and zwitterionic character . Herein, we describe the reaction of 1 with 1,3,4,5‐tetramethylimidazol‐2‐ylidene (NHC Me4 ).…”
Section: Figurementioning
confidence: 99%
“…We recently reported on a bicyclic silicon ring compound Si 4 {N(SiMe 3 )Dipp} 4 1 with two three‐coordinate Si atoms and zwitterionic character . Herein, we describe the reaction of 1 with 1,3,4,5‐tetramethylimidazol‐2‐ylidene (NHC Me4 ).…”
Section: Figurementioning
confidence: 99%
“…That is, this method locates a bond critical point and corresponding bond path running between the bridgehead Ge(1) and Ge(3) atoms (and two ring critical points), which is consistent with the low, yet significant, WBI computed for such a weak interaction. These findings, together with the inspection of the molecular orbitals (MOs) of 9 (see HOMO−1 in Figure below), suggest that a 1,3‐bonding interaction between Ge(1) and Ge(3) can be assumed, a situation which is analogous to that found in its silicon counterpart [Si{N(SiMe 3 )(Dip)}] 4 …”
Section: Resultsmentioning
confidence: 74%
“…The compound can alternatively be prepared on a larger scale, and in good isolated yield, by treating the alkoxy/amido‐germylene DBu LGeO t Bu with HBpin in a σ‐bond metathesis reaction. It is worth noting that similar attempts to hydrogenate the closely related silicon(I) cluster, [Si{N(SiMe 3 )(Dip)}] 4 , were not successful, as the reaction did not proceed, even when it was carried out at 60 °C under 9 bar of H 2 …”
Section: Resultsmentioning
confidence: 99%
“…Sulfur was recrystallized from toluene (PhMe). [Si 4 {N(SiMe 3 )Dipp} 4 ] · 1.5PhMe, red selenium, and ( n Bu) 3 PTe were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…We recently synthesized the bicyclic silicon(I) ring compound [Si 4 {N(SiMe 3 )Dipp} 4 ] 1 and found that it reacts with sulfur (S 8 ) in refluxing toluene in an unprecedented manner to yield [Si 4 S 3 {N(SiMe 3 )Dipp} 4 ] 2 even if an excess of sulfur was used (see Scheme ) . Thus, we investigated the reactivity of 1 with selenium, tellurium, oxygen and the group 16 element compounds Me 3 NO and TeP( n Bu) 3 .…”
Section: Introductionmentioning
confidence: 99%